2019
DOI: 10.1111/acel.12997
|View full text |Cite
|
Sign up to set email alerts
|

Follicle‐stimulating hormone promotes renal tubulointerstitial fibrosis in aging women via the AKT/GSK‐3β/β‐catenin pathway

Abstract: Estrogen withdrawal in aging women contributes to the progression of chronic kidney disease (CKD). However, the effect of high circulating follicle‐stimulating hormone (FSH) levels on renal dysfunction remains unknown. In this study, blood samples from 3,055 postmenopausal women were collected and tested, which showed that there was a strong negative correlation between eGFR and FSH levels (p < 0.001), independent of LH, testosterone, and estradiol. Functional FSHR was detected in renal tubular epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Previous studies have shown that FSH can affect the metabolism of non-gonadal organs such as liver ( 16 , 17 ), adipose tissue ( 33 ), and bone ( 15 , 34 36 ), which is supported by our findings. Moreover, FSH receptor is expressed in kidney tissue ( 37 , 38 ) and FSH was shown to promote renal tubulointerstitial fibrosis in aging women via the protein kinase B (AKT)/glycogen synthase kinase (GSK)‐3β/β‐catenin pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FSH can affect the metabolism of non-gonadal organs such as liver ( 16 , 17 ), adipose tissue ( 33 ), and bone ( 15 , 34 36 ), which is supported by our findings. Moreover, FSH receptor is expressed in kidney tissue ( 37 , 38 ) and FSH was shown to promote renal tubulointerstitial fibrosis in aging women via the protein kinase B (AKT)/glycogen synthase kinase (GSK)‐3β/β‐catenin pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, FSH caused kidney dysfunction and tubulointerstitial fibrosis, and worsening kidney injury through macrophage recruitment and activation. 25 The NRXN1 gene encodes a single-pass type I membrane protein, which is involved in the central nervous system. Variants in this gene have been implicated in blood pressure, body mass index (BMI) and a range of cognitive traits.…”
Section: Discussionmentioning
confidence: 99%
“…The increased activities of ALT, AST, and LDH in the Biolasol + p-FSH group after 2 h of kidney preservation are noteworthy. This probably indicates increased FSHR expression on renal tubular epithelial cells (RECs), which may result in tubulointerstitial fibrosis [19]. Zhang et al, using an ovariectomized mouse model, found that the administration of recombinant FSH at a dose ranging from 0.15 IU to 0.3 IU increases the protein, creatinine, and urea concentrations in the blood serum of the rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al have confirmed the expression of FSHR on renal tubular epithelial cells (RECs) and on endothelial cells of blood vessels [18]. A strong negative correlation has been demonstrated between eGFR (estimated glomerular filtration rate) and FSH activity in renal function tests [19]. The kidneys play an important role in the excretion of FSH [17].…”
Section: Introductionmentioning
confidence: 95%